Pemahaman Guru Fikih terhadap Talfiq Al-Mazhab dalam Pelaksanaan Shalat di Pondok Pesantren Modern Rahmatul Asri - Nurhajrahwati; Bakry, Muammar (Universitas Islam Negeri Alauddin Makassar, 2023)
This paper aims to discuss the analysis of talfiq al-Mazhab for the implementation of prayer and ablution, this study uses a descriptive (qualitative) field study. The results of this study indicate that: in the implementation of worship there is no problem with talfiq (mixing one school with another in the case of worship). religion, especially in terms of worship), but when performing a prayer service using the Shafi'I School and when performing ablution using the Hanafi School, the talfiq issue is not a problem. So, in the fiqh teacher's understanding of talfiq al-Mazhab in the implementation of prayer and ablution at the Rahmatul Asri Modern Islamic Boarding School, it is